The complete mitochondrial genome of long-tailed whiskered bat, Myotis frater (Myotis, Vespertilionidae). Issue 2 (3rd July 2018) - Chung, Chul-Un; Kim, Sung-Chul; Jeon, Young-Shin; Han, Sang-Hoon; Yu, Jeong-Nam
Abstract: Here, we report the complete mitogenome of Myotis frater with the GenBank accession number MH177276 as a first step to elucidate genetic characteristics of this species. Its mitogenome was 17, 089 bp long and consisted of 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a control region. The gene order and composition of M. frater was similar to that of most other vertebrates. The base composition of the 13 PCG in descending order was A (33.8%), C (22.7%), T (30.4%), and G (13.1%), with an AT content of 64.2%. Four overlapping regions in ATP8 / ATP6, ATP6/COX3, ND4L / ND4, and ND5 / ND6, among the 13 PCGs were found. The 935 bp long control region is located between tRNA-Pro and tRNA-Phe with 4 ATTACATAATACATTATATGTATAATCGTACATTAAATTAACTCCCACATGAATATTAAGCATGTCCATACTAATATTAAT-repeat at 5′ region and 45 ACGCAT-repeat at 3′ terminus. Phylogenetic analysis suggested that M. frater is most closely related to M. bechsteinii (KX757757), it was supported by 100% bootstrap under both ML and NJ tree.